Pengaruh Pola Asuh Demokratis Orang Tua terhadap Cara Bergaul Anak: Studi di Desa Derik, Susukan, Banjarnegara - Intan Nur Azizah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
Deviation of children's behavior becomes a social phenomenon of concern. After all, children grow and develop in the family. Every family has a different method of educating. Therefore, it is important to conduct research related to parenting parents, in order to be able to assess its influence the way of socializing children in the society. The method used is quantitative research methods using simple regression analysis techniques. Based on the research conducted, the following results were obtained, parenting democratic parenting had a positive effect on children's ways of getting along. Reality on the ground proves that families who have democratic parenting tend to have children who have warm personalities in society, because they are taught how to respect, give rights to others, carry out obligations and do justice.